Clinical Diagnostic Criteria Have a High Impact on the Frequency of Dementia in Late-Stage Parkinson's Disease - Severiano e Sousa, Catarina; Fabbri, Margherita; Godinho, Catarina; Simões, Rita; Chendo, Inês; Coelho, Miguel; Martins, Isabel Pavão; Ferreira, Joaquim J. (Frontiers in Neurology, 2021)
Background: Cognitive impairment is a potential late feature of Parkinson's disease (PD). However, studies in patients with late-stage PD are lacking due to the particular characteristics of this population. Objectives: To evaluate the frequency of dementia in late-stage PD patients and to assess the impact of using different diagnostic criteria. Methods: We conducted a cross-sectional study to estimate the frequency of dementia in late-stage PD patients using the International Parkinson and Movement Disorders Society (MDS) (Level II) clinical diagnostic criteria as the primary outcome. We also applied other diagnostic criteria [MDS (Level I), DSM-IV, and DSM-5 criteria] to determine their applicability and impact on dementia frequency. Results: 93 participants with a mean age of 75.8 years (SD 6.8) and 16.5 years (SD 7.5) of disease duration were included. 64.3% were classified as demented using the International Parkinson and Movement Disorders Society (MDS) (Level II) clinical diagnostic criteria. We observed a high discrepancy on the frequency of dementia depending on the criteria applied [6.2% with MDS (Level I), 58.8% with DSM-IV, and 72.0% with DSM-5 criteria]. Conclusions: We found a frequency of dementia below what was observed in similar populations. The particular characteristics of our sample may have contributed as protective factors for late-stage dementia. Dementia frequency varied depending on the criteria used mainly due to the presence of major depression.